PEMANFAATAN MEDIA SOSIAL SEBAGAI SUMBER BELAJAR PADA MATA PELAJARAN TEKNOLOGI OTOMOTIF: STUDI LITERATUR - Alief Elsan Ramadhan; Suthan Aliefasha Siregar; Wahid Munawar (STKIP Subang, 2026)
This study aims to analyze the utilization of social media as a learning resource in automotive technology subjects through a literature review method. The research was conducted by collecting and analyzing various scientific journals, research articles, and relevant literature sources related to the research topic. The literature search was carried out through Google Scholar and Garuda databases using keywords related to social media, learning resources, and automotive technology. The selected literature consisted of publications from the last ten yearsThe results indicate that social media plays a positive role in supporting the learning process by increasing students’ motivation, engagement, participation, and understanding of learning materials. Social media also facilitates students' access to more current and interactive information through various digital contents, such as automotive practice videos and tutorial materials. However, the use of social media also presents several challenges, including distractions and the possibility of encountering information with questionable validity. Therefore, the use of social media as a learning resource should be properly guided and monitored to ensure its effective implementation in automotive technology education.